(untitled) (Journal of Pharmaceutical Negative Results, 2023)
With each passing year, there is a rapid increase in mobile data traffic and also there occurs a demand for bringing a higher data rate to a growing number of users. The next generation networks need to depend on denser infrastructure deployment, reduced inter- and intra-cell interference, [2] simple signal processing, and reduced transmitted power, as well as improved energy and spectral efficiency, to provide seamless connectivity. The mathematical modeling of MIMO systems is discussed, with emphasis on the technology's key features. The latest developments in the MIMO area, such as Multi-user MIMO (MU-MIMO) [1], Massive MIMO, and MIMO OFDM techniques, are then discussed in detail, with an emphasis on their importance in cellular communication systems. Massive MIMO has been regarded as the best approaches to increase spectral and energy efficiency in broadband wireless communication systems. The massive MIMO’s channel model must be explored as the first step in evaluating the performance of any communication system.